PEMANFAATAN SISTEM CERDAS IRIGASI SEBAGAI SOLUSI MANAJEMEN IRIGASI DI DESA SUKAJAYA KECAMATAN MALANGBONG KABUPATEN GARUT - Hadikaryana, Oscar; Abdurrohim, Iim; Hariman, Irman; Yasri; Rahman, Alkautsar; Suprihadi, Deni; Atmaja, Subhanjaya Angga; Suharyanto (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
This community service activity was conducted in Sukajaya Village, Malangbong District, Garut Regency, aiming to enhance farmers’ technological literacy through the implementation of a smart irrigation system based on the Internet of Things (IoT) and Artificial Intelligence (AI). The main problem faced by the community is the inefficiency in water use and manual irrigation management. The program employed a Participatory Action Learning (PAL) approach, engaging local farmers in hands-on learning and technology application. The activities consisted of seminars, training sessions, and live demonstrations of an automatic irrigation system integrating soil moisture sensors and IoT modules to regulate watering automatically. Evaluation results indicated a 68% increase in participants’ understanding of smart system concepts and their applications in agriculture. Participants also showed strong enthusiasm to develop similar systems in their own fields. This program demonstrates that participatory-based education effectively bridges the technological gap between universities and rural communities, serving as an initial step toward the adoption of sustainable precision agriculture.